2009
DOI: 10.1111/j.1365-2818.2009.03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending immunofluorescence detection limits in whole paraffin‐embedded formalin fixed tissues using hyperspectral confocal fluorescence imaging

Abstract: SummaryA major problem in microscopic imaging of ex vivo tissue sections stained with fluorescent agents (e.g. antibodies, peptides) is the confounding presence of background tissue autofluorescence. Autofluorescence limits (1) the accuracy of differentiating background signals from single and multiple fluorescence labels and (2) reliable quantification of fluorescent signals. Advanced techniques such as hyperspectral imaging and spectral unmixing can be applied to essentially remove this autofluorescent signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although previous reports detail an observed increase of IL‐1β IR within the dorsal horn of the spinal cord after nerve ligation with chromic gut or silk sutures (Hashizume et al 2000), detecting statistically significant changes in IL‐1β IR has been problematic. Meanwhile, the use of spectral analysis procedures in other studies has demonstrated increased accuracy and sensitivity for the detection of cell‐specific markers (Constantinou et al 2009; Mahad et al 2009; Andres et al 2010). We therefore made direct comparisons between standard fluorescent analysis with Image J software and spectral image analysis software to identify the most sensitive method to quantify immunoreactive proteins of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous reports detail an observed increase of IL‐1β IR within the dorsal horn of the spinal cord after nerve ligation with chromic gut or silk sutures (Hashizume et al 2000), detecting statistically significant changes in IL‐1β IR has been problematic. Meanwhile, the use of spectral analysis procedures in other studies has demonstrated increased accuracy and sensitivity for the detection of cell‐specific markers (Constantinou et al 2009; Mahad et al 2009; Andres et al 2010). We therefore made direct comparisons between standard fluorescent analysis with Image J software and spectral image analysis software to identify the most sensitive method to quantify immunoreactive proteins of interest.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, it will likely be necessary to apply a more rigorous linear spectral-unmixing algorithm, as we have used previously in hyperspectral fluorescence imaging. 13 We are currently investigating this for SERS imaging, using multiple discrete BP filter bands for each reporter. We are also currently implementing a modified version of the instrument, using a fast tuneable narrow BP filter with high transmission efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral imaging has been widely applied since its discovery in various fields, such as food science (Zhu et al 2013;Peng et al 2010), traditional Chinese drug detection (Hang et al 2010;Zhao et al 2010), medical molecular biology (Gendrin et al 2007), and immunofluorescent medicine (Constantinou et al 2009). FSI refers to a technique in which images are collected, displayed, processed, and analyzed through multiple spectral channels.…”
Section: Introductionmentioning
confidence: 98%